2018
DOI: 10.22159/ajpcr.2018.v11i7.25859
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Impact of Berries (Morus Alba and Morus Rubra) Fruit Extract in the Regression of High-Fat Diet-Induced Cardiac Dysfunction in Rats

Abstract: Objective: The aim of the present study is to investigate the effect of Morus alba (MA) and Morus rubra L. (MR) fruit extract on obesity-induced cardiac dysfunction and fibrosis in cardiac tissue.Methods: Seventy male Wistar albino rats were randomly divided into five groups of ten rats each. MA and MR have been administered for 6 weeks in obese rats induced by high-fat diet (HFD). Adiponectin, glucagon, troponin, plasminogen activator inhibitor, cell adhesion molecules-1 (intracellular and vascular respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…These findings showed the capacity of M. alba fruit to manage hyperlipidaemia. In another study, M. alba fruit modulated obesity-induced cardiac dysfunction by inhibiting lipogenesis and fibrosis, and enhancing lipolysis in high-fat diet-induced obesity [ 74 ]. Fruit extract also attenuated reactive oxygen species (ROS), vascular function, inflammatory markers, and lipid accumulation while reducing collagen in obese rats; these are considered factors for defense against and remediation of obesity-related cardiac dysfunction cardiac fibrosis.…”
Section: Nutraceutical Properties Of Morus Albamentioning
confidence: 99%
“…These findings showed the capacity of M. alba fruit to manage hyperlipidaemia. In another study, M. alba fruit modulated obesity-induced cardiac dysfunction by inhibiting lipogenesis and fibrosis, and enhancing lipolysis in high-fat diet-induced obesity [ 74 ]. Fruit extract also attenuated reactive oxygen species (ROS), vascular function, inflammatory markers, and lipid accumulation while reducing collagen in obese rats; these are considered factors for defense against and remediation of obesity-related cardiac dysfunction cardiac fibrosis.…”
Section: Nutraceutical Properties Of Morus Albamentioning
confidence: 99%
“…In this type, the dispersion system is formed by drug incorporation into crystalline carriers such as urea and sugars, creating a slowly releasing thermodynamically stable crystalline SD. [14][15][16] The eutectic mixture was the first SD to be formulated. The monotectic mixture is not favored since the product and carrier melting points are unaffected.…”
Section: First-generation Solid Dispersionmentioning
confidence: 99%
“…The proposed carriers such as Hydroxy Propyl Cellulose (HPC) and Eudragit RS are used to sustain the release of biologically short half-life drugs. 14,25 Solubility enhancement and extending the drug release in a controlled manner are the main targets of the CSRD. 25…”
Section: Fourth-generation Solid Dispersionmentioning
confidence: 99%
“…Fruits of mulberry (Morus alba L. and Morus rubra L.) are rich in polyphenolic compounds such as quercetin, rutin, and 1-deoxynojirimycin. El-Baz et al (2018a) have studied the potential of fruit extract from Morus alba L. and Morus rubra L. to attenuate obesity-induced cardiac dysfunction and fibrosis in rats. Their histopathological experiments have shown that oral administration of the extracts to the obese rats has significantly treated cardiac dysfunction and fibrosis linked to obesity.…”
Section: Polyphenolsmentioning
confidence: 99%